RESPON MASYARAKAT TERHADAP JAMAAH TABLIGH: STUDI KASUS VILLAGE JAMIATUN ULAMA, LAM ILIE TEUNGOH, ACEH BESAR - Nurlaila Nurlaila; Nofal Liata (Prodi Studi Agama-Agama, 2021)
Jamaah tabligh is an organization that was originally pioneered by Maulana Muhammad Ilyas, an 'alim who lives in the north of the Indian capital, New Delhi. In Indonesia, the tabligh congregation began to enter estimated in 1952. The tabligh congregation has genuine motivation, is passionate and has high dedication and sincerity in carrying out Islamic da'wah in society. Tablighi congregations are able to set a good example and even earnestly practice the Sunnah of the Prophet Saw in their daily life. The people of Jamiatul Ulama Village, Indrapuri District, Aceh Besar District have different views on the existence of the tabligh congregation. This study aims to determine how the views of the people of Jamiatul Ulama Village towards the tabligh congregation and the influence of the teachings of the tabligh congregation on the morals of the Jamiatul Ulama Village community. In this study the authors used field research methods (field research) with a qualitative approach that collected data through observation, interviews, documentation. The results showed that the view of the community towards the tabligh congregation was different, there were those who accepted it actively, passively and there were those who did not accept it. The reason they accept it is because of its excellent preaching, morals, and the growing presence of the tabligh congregation in the mosque. The reason for those who do not accept it is because the community views the tabligh congregation as new teachings, lazy to work. With the existence of the community's morality tabligh congregation, a lot has changed, the community is increasingly fond of performing acts of worship, congregational prayers are increasingly living in mosques, and an increasing number of congregations at mosques. However, social activities between the tabligh congregation and the community in Jamiatul Ulama Village are less well-connected.